2019
DOI: 10.1016/j.jhazmat.2018.10.061
|View full text |Cite
|
Sign up to set email alerts
|

Paraffin/red mud phase change energy storage composite incorporated gypsum-based and cement-based materials: Microstructures, thermal and mechanical properties

Abstract: In this study, paraffin/red mud phase change energy storage composites were fabricated at 4 mix proportions with paraffin to red mud ratios of 0.4:0.6, 0.45:0.55, 0.5:0.5, and 0.55:0.45 by a mixed mill-heating method. Scanning electron microscopy (SEM) and Fourier transform infrared (FT-IR) results reveal that paraffin flows well into red mud pores and has good compatibility. The differential scanning calorimetry (DSC) results reveal that the melting temperatures of the paraffin/red mud phase change energy sto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(18 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…Cho et al (2019) showed that TPH can degrade and partition during chemical weathering; gasoline-range organics (C6–C10) and diesel-range organics (DRO; C10–C28), which are the more soluble and volatile compounds, can be transported to other environmental media, while oil-range organics (ORO; C28–C40), which are relatively non-mobile and recalcitrant, remain near the point of release [ 34 ]. A chemical understanding of TPH is helpful in designing an optimal remediation process and for estimating the environmental impact of these TPH [ 35 ]. TPH immobility in soils makes it challenging to dispose of contaminated soils.…”
Section: Discussionmentioning
confidence: 99%
“…Cho et al (2019) showed that TPH can degrade and partition during chemical weathering; gasoline-range organics (C6–C10) and diesel-range organics (DRO; C10–C28), which are the more soluble and volatile compounds, can be transported to other environmental media, while oil-range organics (ORO; C28–C40), which are relatively non-mobile and recalcitrant, remain near the point of release [ 34 ]. A chemical understanding of TPH is helpful in designing an optimal remediation process and for estimating the environmental impact of these TPH [ 35 ]. TPH immobility in soils makes it challenging to dispose of contaminated soils.…”
Section: Discussionmentioning
confidence: 99%
“…Also, a hollow and a porous structure formed by SMs aggregates (Figure 7d,e) was observed, and this structure accounted for the inner−outer superhydrophobic properties of the SMs which supported results regarding hydrophobicity and durability. 53,54 As shown in the particle count distribution of the statistical data (Figure 7f), the median diameter of the particles was centered at ca. 1200 and 2000 nm, respectively.…”
Section: Superhydrophobicity and Durability Of The Sstmentioning
confidence: 85%
“…In addition, organic materials have stable performance, low toxicity and low cost. However, there are also problems in organic materials such as low thermal conductivity, small energy storage density, and easy volatility (Kenisarin, 2014;Liu et al, 2019;Qu et al, 2020;Duan et al, 2021).…”
Section: Introductionmentioning
confidence: 99%